Letter from Georg Bredig to Max Bredig, April 1, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) provides professional advice to his son, Max Bredig (1902-1977), as he contemplates emigrating from Germany amidst increasing hostility towards Jewish citizens under the Third Reich.
Keywords: Third Reich; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Antisemitism; Chemistry; Emigration and immigration